Normal and anomalous codeposition Of Ni-Co-Fe-Zn alloys from EMIC/EG in the presence of an external magnetic field - Ebadi, M.; Mahmoudian, M.R.; Basirun, Wan Jefrey; Alias, Y. (Springer Verlag (Germany), 2011)
The codeposition of Ni-Co-Fe-Zn alloys from a mixture of 1-ethyl-3-methylimidazolium chloride (EMIC)/ethylene glycol (EG) was studied using potentiostatic electrodeposition in the potential range of -1.10 and -1.30 V vs saturated calomel electrode (SCE), using a permanent parallel magnetic field (PPMF) of 9 T. The uniform magnetic field was aligned parallel to the cathode surface. It was found that both normal and anomalous codeposition occurred. Films with different elemental percentage and deposit morphology were obtained from a mixture of EMIC/EG solution at the applied potentials (-1.10 and -1.30 V) in the absence and presence of a PPMF. The influence of magnetic field on the nucleation and growth process is studied with respect to the magneto-hydrodynamic effect (MHD) and applied potentials. © 2011 The Minerals, Metals & Materials Society and ASM International.